The human dimensions of restoring degraded forests and lands : case of Cameroon - Nsubuga, F.W.N. (Francis Wasswa Nkugwa) (University of Pretoria, 2023)
Thesis (PhD (Environment and Society))--University of Pretoria, 2023.